2015
DOI: 10.1242/dmm.019414
|View full text |Cite
|
Sign up to set email alerts
|

The role of mTOR signaling in the regulation of protein synthesis and muscle mass during immobilization in mice

Abstract: The maintenance of skeletal muscle mass contributes substantially to health and to issues associated with the quality of life. It has been well recognized that skeletal muscle mass is regulated by mechanically induced changes in protein synthesis, and that signaling by mTOR is necessary for an increase in protein synthesis and the hypertrophy that occurs in response to increased mechanical loading. However, the role of mTOR signaling in the regulation of protein synthesis and muscle mass during decreased mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 57 publications
8
109
0
2
Order By: Relevance
“…In these studies, using radioactive methods, Loughna et al estimated the fractional rate of protein synthesis [7], and Fluckey et al assessed the rate of protein synthesis in vitro [8,9]. The use of in vivo SUnSET technique, which was applied in our study, has shown a decrease in the protein synthesis rate in soleus muscle of mice after 7 days of hindlimb immobilization [32]. The general interest of our study was to identify the possible intracellular mechanisms/ pathways that could be implicated in a decline in protein synthesis rate in rat soleus by the 3 rd day of hindlimb unloading.…”
Section: Discussionmentioning
confidence: 57%
“…In these studies, using radioactive methods, Loughna et al estimated the fractional rate of protein synthesis [7], and Fluckey et al assessed the rate of protein synthesis in vitro [8,9]. The use of in vivo SUnSET technique, which was applied in our study, has shown a decrease in the protein synthesis rate in soleus muscle of mice after 7 days of hindlimb immobilization [32]. The general interest of our study was to identify the possible intracellular mechanisms/ pathways that could be implicated in a decline in protein synthesis rate in rat soleus by the 3 rd day of hindlimb unloading.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, numerous studies demonstrated that a reduction in muscle protein fractional synthesis rate (FSR) occurs in the first days of immobilization [53,75,76]. This rapid reduction of protein synthesis persists for several weeks since a decrease of muscle FSR has been also reported in human skeletal muscle after 14 and 28 days of bed rest [77,78].…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 99%
“…Interestingly, skeletal muscle exhibits alteration in PI3K/Akt/mTORC1 axis during immobilization [75,76,[80][81][82]. This phenomenon, called anabolic resistance, emphasizes the reduced response to anabolic stimuli [80,82].…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 99%
“…Além da metionina, ocorre a participação de uma proteína conhecida como mTOR (mammalian target of rapamycin), considerada um fator chave da síntese proteica no músculo esquelético, por regular numerosos componentes envolvidos na síntese proteica, incluindo fatores de iniciação e elongação (Wang & Proud, 2006, You et al, 2015. Essa proteína quinase exerce um papel fundamental na regulação do crescimento muscular, e vários estudos evidenciaram a importância da mTOR como mediador central do metabolismo e crescimento (Yang et al, 2008).…”
Section: Mecanismos Envolvidos Na Síntese Proteicaunclassified
“…Na fase de alongamento, o polipeptídeo formado é alongado pela adição de unidades sucessivas de AA ligadas covalentemente, oriundas da ligação entre o códon do mRNA e o anticódon do tRNA (Rudorf & Lipowsky, 2015). Este processo requer fatores de alongamento, regulados pela mTOR (Wang & Proud, 2006, You et al, 2015 e hidrólise de GTP.…”
Section: Mecanismos Envolvidos Na Síntese Proteicaunclassified